Kinetic and Mechanistic Observations on the Photoinduced Isomerization Reaction of Organometallic Chalcones: A Steady State and Flash Photolysis Study - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Maldonado-Hernandez, T; Maldonado-Hernandez, T (Wiley-VCH Verlag, 2018)
The photoinduced isomerization (E to Z) processes of a new series of organometallic chalcones derived from cyrhetrene, ferrocene and cymantrene functionalized with a benzo or 4′-benzo-15-crown-5 moiety were studied in acetonitrile. The influence of near-UV steady-state irradiation on the properties of the chalcones was followed by means of UV/Vis absorption and 1H NMR spectroscopy. Time-resolved ultrafast transient absorption and nanosecond flash photolysis spectroscopic studies revealed that irradiation of E-cyrhetrenyl chalcones (1 a, b) led to the formation of an intermediate excited state which evolves irreversibly into the Z isomer. A second excited state, formed in the picosecond timescale, is responsible for the luminescence of the cyrhetrenyl chalcone 1 b. The photoisomerization mechanism was found to be different for the ferrocenyl chalcones (2 a, b) compared to the E-cyrhetrenyl chalcones (1 a, b). For the ferrocenyl chalcones, minimal concentrations of the Z isomer are formed and an excited state, assigned as a metal-to-ligand charge transfer excited state, leads to the formation of another product of reaction. The photoisomerization processes of the complexes, as seen through the values of the quantum yields and rate constants, are affected by the steric hindrance created by the macrocycle as well as the perturbation of the electronic system by metal ions, such as Ca2+, coordinated to the macrocycle. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim